(untitled) (Revista Torreón Universitario, 2015)
This document contains the proposal of a new evaluation model for the professorate in FAREM-Carazo, which contributes to extend the process of evaluation as a mean of reflection and improvement for the professorate in the teaching components. For the elaboration of the diagnostic instrument, the necessity of applying two types of questionnaire with open questions was considered, this was with purpose of getting high quality information of the academic government units and the professorate. The implementation of the spider web instrument that comprises the teaching, investigation, management and extension aspects was validated and applied to the professorate by head department directors. The professorate showed acceptance to the instrument applied, and above all, the huge necessity of strengthening the investigation aspect and the management level of the professorate and faculty authorities was evidenced.